The role of ceramide and SEW 2871 in the transcription of enzymes involved in amyloid b precursor protein metabolism in an experimental model of Alzheimer’s disease - Kinga Czubowicz; Sylwia Wójtowicz; Przemysław Leonard Wencel; Robert Piotr Strosznajder (Folia Neuropathologica, 2018)
Alzheimer’s disease (AD) is characterized by alterations of amyloid precursor protein (APP) metabolism, accumulation of amyloid  peptides (A), hyperphosphorylation of Tau proteins and also by sphingolipids disturbances. These changes lead to oxidative stress, mitochondria dysfunction, synaptic loss and neuro-inflammation. It is known that A may promote ceramides formation and reversely, ceramides could stimulate A peptides release. However, the effect of ceramide and sphingosine-1-phosphate (S1P) on APP metabolism has not been fully elucidated. In this study we investigated the role of ceramide and S1P on APP metabolism. Moreover, the effect of ceramide and SEW 2871 (agonist for S1P receptor-1) on Sirt1 (NAD+-dependent nuclear enzyme responsible for stress response) gene expression under A toxicity was analyzed. Experiments were carried out using pheochromocytoma cells (PC-12) transfected with: an empty vector (used as a control), human wild-type APP gene (APPwt) and Swedish mutated (K670M/N671L) APP gene (APPsw). Our results indicated that C2-ceramide significantly decreased the viability of the APPwt, APPsw as well as empty vector-transfected PC12 cells. It was observed that C2-ceramide had no significant effect on the mRNA level of - and -secretase in APPwt and APPsw cells. However, it significantly decreased transcription of -secretase in control cells. Results also showed a significant increase in Psen1 (crucial subunit of -secretase) gene expression in APPsw cells after incubation with C2-ceramide. We observed that SEW 2871 significantly upregulated the mRNA level of -secretase in control-empty vector-transfected cells subjected to C2-ceramide toxicity. The same tendency, though insignificant, was observed in APPwt and APPsw cells. Moreover, SEW 2871 enhanced the mRNA level of -secretase and Psen1 in APPsw cells after C2-ceramide treatment. Additionally, SEW 2871 significantly upregulated a gene expression of Sirt1 in APPwt and also APPsw cells subjected to C2-ceramide toxicity. Furthermore, it was observed that SEW 2871 significantly enhanced the viability of all investigated cells’ lines probably through its positive influence on Sirt1.